Participatory Black Scurf Disease Management on Potato in Nepal - Sharma, Buddhi P.; KC, Ram B. (Nepal Agriculture Research Journal, 2014)
A farmer's participatory field experiment was accomplished during three consecutive years (2003-2005) for the sustainable management of black scurf disease of potato at Mainapokhar, Bardiya, Nepal. A heavily infested field with Rhizoctonia solani was selected prior to experimentation. Experiment was laid out in randomized complete block design with three replications. The efficacy of two concentrations (2% and 3%) of boric acid and 0.15% of Thiophanate Methyl were tested for disease control through seed treatment. An antagonistic fungus Trichoderma harzianum was used as seed and soil treatment. As per treatment plan some plots were sterilized with formaldehyde 1% prior to planting. The plots having healthy seed (pre-basic seed) planted in sterilized plots showed minimum disease(6.8%) followed by 3% boric acid treated seed planted in sterilized plots (10.8%) and 2% boric acid without soil sterilization (13.1%) and seed and soil treated plot with T. harzianum (17.1%). Farmers did not accept treatments connected with soil sterilization by Formalin. After analyzing the overall results of three years experiment farmers choose seed treatment with 2% boric acid prior to planting and identified application of Trichoderma harzianum for black scurf management as second option. Nepal Agric. Res. J. Vol. 8, 2007, pp. 56-62 DOI: http://dx.doi.org/10.3126/narj.v8i0.11581